An improved method for large scale generation and high-throughput functional characterization of human iPSC-derived microglia - Padmakumar, Manisha; Biesmans, Steven; Valadas, Jorge S.; Detrez, Jan R.; Gillet, Gaëlle; Bresler, Priscillia; Clénet, Marie-Laure; Kadiu, Irena (Frontiers in Drug Discovery, 2023)
Neuroscience drug discovery has faced significant challenges due to limited access to relevant human cell models and the translatability of preclinical findings to human pathophysiology. Induced pluripotent stem cells (iPSCs) have emerged as a promising solution, offering the potential to generate patient-specific cell types, including in the recent years, iPSC-derived microglia (iMGL). The current methods rely on complex and time-consuming differentiation procedures, leading to considerable batch-to-batch variability and hindering the establishment of standardized and reproducible high throughput functional screening approaches. Addressing these challenges is crucial in ensuring the generation of homogenous iMGL populations with consistent functional properties. In this study we describe an improved high yield protocol for generation iMGL which allows for increased reproducibility and flexibility in the execution of high throughput functional screens. We introduce a two-step process in embryoid bodies (EBs) maintenance and a stop point allowing cryopreservation at the hematopoietic progenitor cell (iHPC) stages. Furthermore, we demonstrate inter-operator robustness of this modified protocol in a range of high throughput functional assays including phagocytosis, lysosomal acidification, chemotaxis, and cytokine release. Our study underscores the importance of quality control checks at various stages of iPSC-differentiation and functional assay set up, highlighting novel workarounds to the existing challenges such as yield, flexibility, and reproducibility critical for drug discovery.